XPS of PEG-functionalised ionic liquids: towards chlorozincate-based systems - Dick, J.E. (2019)
X-ray photoelectron spectroscopy (XPS) has been utilised to investigate the influence of poly(ethylene glycol) (PEG) substituents on fundamental interactions in ionic liquids (ILs). A series of monocationic and dicationic PEG-functionalised IL systems that are based upon imidazolium, pyridinium and pyrrolidinium cation have been investigated. A robust C 1s fitting model has been developed for all PEG-functionalised ILs investigated and comparison made to their alkyl substituted analogues. A systematic study of the PEG-functionalised IL has revealed a significant difference in the electronic structures of the compound where the first oxygen in an alkyl is moved from the Beta to the alpha position.